2015
DOI: 10.1051/ocl/2015004
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of oils from press cakes by CO2-based technology

Abstract: -In a context of a strong demand for vegetable oils, the development of new "green" processes is essential to provide methods that avoid the use of organic solvents, work at relatively low temperatures and preserve the quality of the final products. The supercritical fluid extraction (SFE) process meets these objectives. In this study, five meals (hemp, flax, sesame, poppy and walnut) were subjected to SFE at 45• C and 250 bar in the presence of ethanol as co-solvent. Using this method, between 77 and 98% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, Date et al, (2015) revealed the extracted oil obtained from pressed sesame seed cake using supercritical CO 2 extraction contained high amount of sesamin and sesamolin, accounted for ~24 mg/g oil. Bardeau et al, (2015) extracted residual oil from five press cakes (hemp, flax, sesame, poppy and walnut) under supercritical CO 2 extraction process with using ethanol as co-solvent. For sesame cake, the supercritical CO 2 extraction could recover residual oil ~56%.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Date et al, (2015) revealed the extracted oil obtained from pressed sesame seed cake using supercritical CO 2 extraction contained high amount of sesamin and sesamolin, accounted for ~24 mg/g oil. Bardeau et al, (2015) extracted residual oil from five press cakes (hemp, flax, sesame, poppy and walnut) under supercritical CO 2 extraction process with using ethanol as co-solvent. For sesame cake, the supercritical CO 2 extraction could recover residual oil ~56%.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…However, the efficiency and selectivity of supercritical CO 2 extraction highly depends on the extraction factors and conditions, for example, extraction pressure and temperature. Although the effect of the process factors on extraction yield of sesame seed oil has been investigated (Bardeau et al, 2015;Corso et al, 2010;Döker et al, 2010;Hu et al, 2004), the effect on physicochemical properties and its bioactive compounds have less studied. Therefore, this research aims to extract residual oil from pressed sesame seed cake using supercritical CO 2 extraction method.…”
Section: Practical Applicationsmentioning
confidence: 99%
“… increasing demand for oilseeds for biofuel production and other technical needs. The analysis of foreign research in the field of oilseeds processing has shown that the main research is aimed at using by-products of oilseeds processing-oil cake and meal as an energy source [5,6], the search for alternative uses of organic solvents for oil extraction [7,8], the study of products in the form of protein feeds obtained during oil extraction to replace more expensive feed ingredients [9], the search for technologies for obtaining food products such as polyphenols, isolates and hydrolysates of oil cake proteins, etc. [10].…”
Section: Introductionmentioning
confidence: 99%
“…-Use of alternative solvents as supercritical fluids, alcohols, aqueous mixes (Bardeau et al, 2015;Phan et al, 2009;Russin et al, 2011;Sicaire et al, 2015). -Use of new technological approaches as enzymes cocktails (Rosenthal et al, 1996) or ultrasounds (Vilkhu et al, 2008).…”
Section: Specific Case Of Oilseed Cakes: Impact Of De-oiling Pretreatmentioning
confidence: 99%